Rozwiąż:

a)x²+3x-18=(2x-16)(2x+1)
b)-4x²+12x-9≤0
c)x²-6x+9≤-x+5
d)4I3x-1I+2I-3+5I=I∛(27-1)I
e)(x-1)³+(2x+3)³=27x³+8
f)(x+1)(x²+2)+(x+2)(x²+1)=2
g)(2x-4)(x-1)(5-x)(6+x)<0
h)(x²-x-6)(x²+2x+3)≤0
i)(16-x²)(x²+4)(x²+x+1)(x²-x-3)≤0
j)x⁴+8x³+12x²≥0
k)x³-3x²+3x-9≤0
l)x³-x²-14x+24<0
l){(3x+3)/(3y-2)=1
{x(2y-5)-2(x+3)y=2x+1
Układ równań-metoda podstawiania, wyznaczników i przeciwnych współczynników

1

Odpowiedzi

2009-12-30T09:59:56+01:00
B)-4x²+12x-9≤0
delta=b2 - 4ac=144-144=0
x=-b/2a=-12/-8=11/2=1,5

c)x²-6x+9≤-x+5
x2-6x+9+x-5<0
x2-5x+4<0
delta=b2-4ac=25-16=9
x1=4
x2=1